Gum Resin and Forest Research - Saksena, K. B. (Indian Forester, 1952)
To-day the pioneer in the field of Gum Naval Stores Industry is the United States of America. Through decades of patient and plodding research work in this field they have made the most far reaching improvements in their working technique in the forests as well as in the processing plants. A great deal of work shall have to be done in India if we want our resin industry to prosper and our forest wealth to be conserved in the best possible way.